Theoretical dilemmas of criminal law in the aspects of canon law and secular law: Interview with Péter Erdő, archbishop of Esztergom-Budapest (Academic Journal of Internal Affairs, 2021)
Cardinal Péter Erdő has been archbishop of the main diocese Esztergom-Budapest, primate of Hungary and the highest leader of the Hungarian catholic church from 2002. Beside his high-ranking ecclesiastical role assumption in the church, he has fulfilled a high volume of work in the world of sciences, too. He is ordinary member of the Hungarian Academy of Sciences and president of the Scientific Academy „Szent István”. He has written numerous scientific books- both in Hungarian and in several foreign languages –in his latest book titled „The Soul of Canon Law” he presents the valid catholic canon law and its historical development. His special research area is canon law, the history of canon law in the Middle Age and the history of the church. The topic of several of his works is the examination of the connection of sin and felony and their theoretical questions. He is active participant of the international scientific public life of canon law, and board member of several international scientific bodies. In the topic of canon law, he is an unavoidable authority not only in Hungary but also internationally. „He is deeply interested in law history, in the human relations of canon law, he is not only interested in the change of rules but also in their backgrounds.” „There are a few people only who can like law in a human way” – said his former teacher about him. It is not a coincidence that Cardinal Péter Erdő in addition to his ecclesiastical duties in the classical sense, has taken and continues to play a major role in the field of ecclesiastical law in both research and education. At the opening of this year’s ecumenic orison week he said in his speech: „Today we especially need to protect and help families. Even if the external environment aggravates sometimes the life of our families, the more we have to stand forthem with generous love.” (URL1). As the highest church leader of the country, he has taken every opportunity to encourage believers and non-believers alike to endure and deal with the special situation caused by the pandemic. In September 2020 the church leaders conducted a meeting – on initiative of Dr. Sándor Pintér, Minister of the Interior – about developments and experiences of the program „Catching up settlements”. Among others we asked Cardinal Péter Erdő how he considers the social role-taking of the Hungarian Catholic Church especially with regard to the pandemic, what he thinks about the connection of canon law and secular law. The interview was conducted by Zsuzsanna Hornyik.
Keywords: criminal law; interview